Expansion of circulating stem-like CD8+ T cells by adding CD122-directed IL-2 complexes to radiation and anti-PD1 therapies in mice - Kateryna Onyshchenko; Ren Luo; Elena Guffart; Simone Gaedicke; Anca-Ligia Grosu; Elke Firat; Gabriele Niedermann (Nature Communications, 2023)
Abstract Combination of radiation therapy (RT) with immune checkpoint blockade can enhance systemic anti-tumor T cell responses. Here, using two mouse tumor models, we demonstrate that adding long-acting CD122-directed IL-2 complexes (IL-2c) to RT/anti-PD1 further increases tumor-specific CD8+ T cell numbers. The highest increase (>50-fold) is found in the blood circulation. Compartmental analysis of exhausted T cell subsets shows that primarily undifferentiated, stem-like, tumor-specific CD8+ T cells expand in the blood; these cells express the chemokine receptor CXCR3, which is required for migration into tumors. In tumor tissue, effector-like but not terminally differentiated exhausted CD8+ T cells increase. Consistent with the surge in tumor-specific CD8+ T cells in blood that are migration and proliferation competent, we observe a CD8-dependent and CXCR3-dependent enhancement of the abscopal effect against distant/non-irradiated tumors and find that CD8+ T cells isolated from blood after RT/anti-PD1/IL-2c triple treatment can be a rich source of tumor-specific T cells for adoptive transfers.